2023
DOI: 10.1002/jmv.28656
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of cervical carcinoma identifies Alpelisib as a therapeutic option for PIK3CA‐mutant cervical carcinoma via the PI3K/AKT pathway

Abstract: Cervical carcinoma is a serious type of gynecological cancer that can affect women of all ages. Cervical carcinoma presents challenges for precision medicine, as not all tumors have specific gene mutations or alterations that can be targeted with existing drugs. Nonetheless, there are some promising targets in cervical carcinoma. Herein, genomic mutation data from The Cancer Genome Atlas and Catalogue of Somatic Mutations in Cancer were used to identify genomic targets for cervical carcinoma. PIK3CA was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…For instance, Dactolisib, a dual PI3K and mTORC1/2 inhibitor has shown potential benefits in CC treatment 45 . Erlotinib treatment sensitizes CSCs to paclitaxel treatment in vitro and in vivo 46 , Alpelisib demonstrates antitumor effects and enhances cisplatin efficacy through the PI3K/AKT pathway in PIK3CA mutant CC cells 47 . The expression of AL021707.6 as well as ZSCAN16-AS1 showed interesting correlation with the IC 50 of these drugs, indicating a new direction in the study of targeting drugs in CC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Dactolisib, a dual PI3K and mTORC1/2 inhibitor has shown potential benefits in CC treatment 45 . Erlotinib treatment sensitizes CSCs to paclitaxel treatment in vitro and in vivo 46 , Alpelisib demonstrates antitumor effects and enhances cisplatin efficacy through the PI3K/AKT pathway in PIK3CA mutant CC cells 47 . The expression of AL021707.6 as well as ZSCAN16-AS1 showed interesting correlation with the IC 50 of these drugs, indicating a new direction in the study of targeting drugs in CC.…”
Section: Discussionmentioning
confidence: 99%
“…At present, molecular therapies targeting PI3K/AKT and MAPK signaling pathways are being extensively investigated for CC treatment. Preclinical studies have demonstrated that PI3K/AKT/mTOR pathway can be inhibited by Alpelisib, leading to the suppression of proliferation and migration of CC cells with PIK3CA mutations [ 57 ]. A novel polysaccharide of Rosa rugosa induced autophagy-mediated apoptosis in human CC cells primarily via the PI3K/AKT/mTOR pathway [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is one of the most common gynecological malignancies. It has both high morbidity and mortality, with an estimated 604 000 new cases and 342 000 deaths worldwide in 2020 1,2 . Human papilloma virus (HPV) is the major cause of cervical cancer, and 12 oncogenic types have been classified as group 1 carcinogens by the International Agency for Research on Cancer Monographs 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It has both high morbidity and mortality, with an estimated 604 000 new cases and 342 000 deaths worldwide in 2020. 1,2 Human papilloma virus (HPV) is the major cause of cervical cancer, and 12 oncogenic types have been classified as group 1 carcinogens by the International Agency for Research on Cancer Monographs. 3 At present, hysterectomy and adjuvant chemo-and radiotherapy are the main treatments for early-and advanced-stage cervical cancer, respectively.…”
Section: Introductionmentioning
confidence: 99%